Multipurpose high-pressure high-temperature diamond-anvil cell with a novel high-precision guiding system and a dual-mode pressurization device - Pippinger, Thomas; Miletich-Pawliczek, Ronald; Burchard, Michael (Review of scientific instruments, 2011)
A novel diamond-anvil cell (DAC) design has been constructed and tested for in situ applications at high-pressure (HP) operations and has proved to be suitable even for HP sample environments at non-ambient temperature conditions. The innovative high-precision guiding mechanism, comparable to a dog clutch, consists of perpendicular planar sliding-plane elements and is integrated directly into the base body of the cylindrically shaped DAC. The combination of two force-generating devices, i.e., mechanical screws and an inflatable gas membrane, allows the user to choose independently between, and to apply individually, two different forcing mechanisms for pressure generation. Both mechanisms are basically independent of each other, but can also be operated simultaneously. The modularity of the DAC design allows for an easy exchange of functional core-element groups optimized not only for various analytical in situ methods but also for HP operation with or without high-temperature (HT) application. For HP-HT experiments a liquid cooling circuit inside the specific inner modular groups has been implemented to obtain a controlled and limited heat distribution within the outer DAC body.